The human squamous oesophagus has widespread capacity for clonal expansion from cells at diverse stages of differentiation. Issue 1 (26th February 2014) - Barbera, Mariagnese; di Pietro, Massimiliano; Walker, Elaine; Brierley, Charlotte; MacRae, Shona; Simons, Benjamin D; Jones, Phil H; Stingl, John; Fitzgerald, Rebecca C
Abstract : Objective: Knowledge of the cellular mechanisms involved in homeostasis of human squamous oesophagus in the steady state and following chronic injury is limited. We aimed to better understand these mechanisms by using a functional 3D approach. Design: Proliferation, mitosis and the expression of progenitor lineage markers were assessed in normal squamous oesophagus from 10 patients by immunofluorescence on 3D epithelial whole mounts. Cells expressing differential levels of epithelial and progenitor markers were isolated using flow cytometry sorting and characterised by qPCR and IF. Their self-renewing potential was investigated by colony forming cells assays and in vitro organotypic culture models. Results: Proliferation and mitotic activity was highest in the interpapillary basal layer and decreased linearly towards the tip of the papilla (p<0.0001). The orientation of mitosis was random throughout the basal layer, and asymmetric divisions were not restricted to specific cell compartments. Cells sorted into distinct populations based on the expression of epithelial and progenitor cell markers (CD34 and EpCAM) showed no difference in self-renewal in 2D culture, either as whole populations or as single cells. In 3D organotypic cultures, all cell subtypes were able to recapitulate the architecture of the tissue of origin and the main factor determining the success of the 3D culture was the number of cells plated, rather than the cell type. Conclusions: Oesophageal epithelial cells demonstrate remarkable plasticity for self-renewal. This situation could be viewed as an ex vivo wounding response and is compatible with recent findings in murine models.